Performance of the Active Microring Resonator Based on SOI Rib Waveguide - Mardiana, Bidin; Haroon, Hazura; Hanim, Abdul Razak; Sahbudin, Saari; Menon, P.S; Abdullah, H. (Trans Tech Publications Inc, 2012)
Micro-ring resonator based on silicon-on-insulator (SOI) has been extensively studied due to its many advantages, thus promising to improve the optoelectronic integrated circuit performance. This paper highlights the study of the free carrier injection effect on the silicon rib waveguide with p-i-n diode structure integrated in the SOI micro-ring resonator. The free carrier concentrations have been modulated by the electrical signal that can cause change of refractive index of the micro-ring resonator. The device performances are predicted by using numerical modelling software 2D SILVACO and Finite Difference Time Domain method simulation software RSOFT. The results show the change of refractive index is maximized at a greater applied voltage. A shift in resonant wavelength of around 6.7 nm was predicted at 0.9V with 1.14x10-3 refractive index change. It is also shown that 8.5dB change of the output response obtained through the output.